Cognitive Training at a Young Age Attenuates Deficits in the zQ175 Mouse Model of HD - Curtin, Paul C. P.; Farrar, Andrew M.; Oakeshott, Stephen; Sutphen, Jane; Berger, Jason; Mazzella, Matthew; Cox, Kimberly; He, Dansha; Alosio, William; Park, Larry C.; Howland, David; Brunner, Daniela (Frontiers in Behavioral Neuroscience, 2016)
Huntington’s Disease (HD) is a progressive neurodegenerative disorder that causes motor, cognitive, and psychiatric symptoms. In these experiments, we tested if operant training at an early age affected adult cognitive deficits in the zQ175 KI Het (zQ175) mouse model of HD. In Experiment 1 we trained zQ175 mice in a fixed-ratio/progressive ratio (FR/PR) task to assay learning and motivational deficits. We found pronounced deficits in response rates and task engagement in naïve adult zQ175 mice (32-33 weeks age), while deficits in zQ175 mice trained from 6-7 weeks age were either absent or less severe. When those mice were re-tested as adults, FR/PR performance deficits were absent or otherwise less severe than deficits observed in naïve adult zQ175 relative to wild type (WT) mice. In Experiment 2, we used a Go/No-go operant task to assess the effects of early cognitive testing on response inhibition deficits in zQ175 mice. We found that zQ175 mice that began testing at 7-8 weeks did not exhibit deficits in Go/No-go testing, but when re-tested at 28-29 weeks age exhibited an initial impairment that diminished with training. These transient deficits were nonetheless mild relative to deficits observed among adult zQ175 mice without prior testing experience. In Experiment 3 we trained mice in a two-choice visual discrimination test to evaluate cognitive flexibility. As in prior experiments, we found performance deficits were mild or absent in mice that started training at 6-9 weeks of age, while deficits in naive mice exposed to training at 28-29 weeks were severe. Re-testing mice at 28-29 weeks age, were previously trained starting at 6-9 weeks, revealed that deficits in learning and cognitive flexibility were absent or reduced relative to effects observed in naive adults. In Experiment 4, we tested working memory deficits with a delayed non-match to position (DNMTP) test. Mice with prior experience exhibited mild working memory deficits, with males zQ175 exhibiting no deficits, and females performing significantly worse than WT mice at a single delay interval, whereas naive zQ175 exhibited severe delay-dependent deficits at all intervals exceeding 1 s. In sum, these experiments indicate that CAG-dependent impairments in motivation, motor control,